Parenting and Emotional and Behavioral Difficulties in a General Population Sample of Adolescents: The Mediating Role of Emotional Dysregulation - Martina Smorti; Annarita Milone; Luisa Fanciullacci; Alessia Ciaravolo; Carmen Berrocal (MDPI AG, 2024)
Research has shown that both parenting and emotional dysregulation are associated with mental health outcomes in youth. This cross-sectional research was developed to replicate these noted findings and explore the mediating role of emotional dysregulation to explain the relationship between parenting and emotional and behavioral difficulties (internalizing and externalizing problems) in adolescents. A total of 104 adolescents (61.5% females; M = 15.62 yrs., SD = 1.38) participated in the study. Participants completed the Parental Bonding Instrument (measuring care, promotion of autonomy, and overprotection) referring to both the mother and father, the Difficulties in Emotion Regulation Scale, and the Youth Self-Report. The results showed that difficulties in emotion regulation fully mediated the relationship between overprotection (in both parents) and low maternal care with internalizing problems, on the one hand, and the relationship between maternal overprotection and low care (in both parents) with externalizing problems, on the other hand. Furthermore, emotional dysregulation partially mediated the effect of paternal care on internalizing problems. These findings help to clarify one of the mechanisms through which parenting can affect mental health in youth. Theoretical and clinical implications are discussed.